1988
DOI: 10.1128/aem.54.8.2078-2085.1988
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Adhesive Holdfast of Marine and Freshwater Caulobacters

Abstract: Caulobacters are prosthecate (stalked) bacteria that elaborate an attachment organelle called a holdfast at the tip of the cellular stalk. We examined the binding of lectins to the holdfasts of 16 marine Caulobacter strains and 10 freshwater species or strains by using a panel of fluorescein-conjugated lectins and fluorescence microscopy. The holdfasts of all the marine isolates bound to only wheat germ agglutinin (WGA) and other lectins that bind N-acetylglucosamine (GlcNac) residues. The freshwater caulobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
127
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 37 publications
(36 reference statements)
0
127
0
Order By: Relevance
“…Interestingly, molecules similar to core NF are involved in non-signalling functions in other bacteria. For example, N-acetylglucosamines are reported to act as adhesins not only in Staphylococcus species (Heilmann et al, 1996;Götz, 2002), but also in Caulobacter crescentus (Merker and Smit, 1988;Ong et al, 1990). In the latter, N-acetylglucosamines are localized to the holdfast of the stalked cells, promoting cell-to-cell adhesion (rosette formation) and adherence to abiotic surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, molecules similar to core NF are involved in non-signalling functions in other bacteria. For example, N-acetylglucosamines are reported to act as adhesins not only in Staphylococcus species (Heilmann et al, 1996;Götz, 2002), but also in Caulobacter crescentus (Merker and Smit, 1988;Ong et al, 1990). In the latter, N-acetylglucosamines are localized to the holdfast of the stalked cells, promoting cell-to-cell adhesion (rosette formation) and adherence to abiotic surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…We compared YB3079 to the podJ transposon mutant YB2863. Wild-type Caulobacter are known to bind to polystyrene and to the lectin wheat germ agglutinin (WGA) (Merker and Smit, 1988). Table 1 and Fig.…”
Section: Cells Express Multiple Forms Of Podjmentioning
confidence: 99%
“…The fluorescent lectin-binding assay was used to visualize the holdfast by fluorescence microscopy using wheat germ agglutinin conjugated to fluorescein (Molecular Probes) (Merker and Smit, 1988;Janakiraman and Brun, 1999). Epifluorescence photomicroscopy was performed on a Nikon Eclipse E800 light microscope equipped with a Nikon B-2E FITC filter cube for FITC and a 100 ¥ plan Apo oil objective (NA 1.4).…”
Section: Detection Of the Holdfast With Fluorescein-labelled Lectinmentioning
confidence: 99%
“…The exact composition of the holdfast is not known; however, lectin binding studies have established that polysaccharides are part of the binding components of the holdfast. Binding and competition experiments with wheat germ agglutinin (WGA) lectin have indicated that the holdfast contains N -acetylglucosamine (GlcNAc) oligomers (Merker and Smit, 1988;Ong et al ., 1990). Treatment of cells with chitinase or lysozyme, enzymes that cleave oligomers of GlcNAc, disrupted rosettes, indicating that the integrity of the GlcNAc is required for holdfast binding (Merker and Smit, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation